Post-Translational Modification of p62: Roles and Regulations in Autophagy - Shuai Xiao; Yeping Yu; Meng Liao; Dandan Song; Xiaozhen Xu; Lingli Tian; Rui Zhang; Hao Lyu; Dong Guo; Qi Zhang; Xing-Zhen Chen; Cefan Zhou; et al. (Cells, 2025)
Autophagy is a highly conserved cellular process that plays a crucial role in maintaining cellular homeostasis by degrading damaged organelles, misfolded proteins, and other cellular components. p62/SQSTM1 functions as a selective autophagy receptor by binding polyubiquitinated cargo through its UBA domain and linking it to microtubule-associated protein light chain 3 (LC3)-decorated autophagosomes. Moreover, p62 acts as a signaling hub and is essential in response to various stressors, including nutrient deprivation and oxidative stress. Post-translational modifications (PTMs) critically regulate p62’s multifaceted roles, controlling p62’s phase separation, cargo recruitment, signaling interactions, and autophagic degradation efficiency. The dysregulation of p62 PTMs is closely related to the occurrence and development of human diseases, particularly neurodegenerative disorders and certain cancers. This review summarizes the main PTM events of p62 discovered to date that influence the autophagy process, including phosphorylation, acetylation, ubiquitination, and S-acylation, as well as their known contributions to protein aggregation and disease. The PTMs of p62 dynamically regulate autophagy, protein aggregation, and cellular signaling, underscoring its importance as a potential therapeutic target and biomarker for these diseases.